Finger Design For Anthropomorphic Prosthetic Hands - (:unkn) unknown (IEEE, 2014)
The prototype of a human hand can be has anthropomorphic features when considering the complex structure (anatomy) of the human hand with all its joints, muscles, tendons and their connection. In this study as a starting point an anthropomorp hic approach is proposed for the mechanical design of the index finger. For this purpose the mechanical structures of the index finger are reproduced in both real and virtual environments. The results for the simulation and prototype are then compared with each other and the human index finger.